Empirical study on effects of website optimization performance techniques under HTTP/2 - Čegan, Lukáš (My University, 2017)
HTTP/1.1 has been used as a generic protocol for communication between client and server for around 25 years. During the year 2015 the second version of HTTP/2 was introduced, which brought major changes in the design of the protocol. Unfortunately, these changes may have both a positive and negative impact on the performance of traditional optimization techniques. In this paper we present an empirical study on effects of the traditional HTTP/1.1 website optimization performance technique under HTTP/2. This study includes Domain sharing, CSS spriting and Inline resource techniques.
Empirická studie účinnosti optimalizace technik výkonu webových stránek pod HTTP/2
Keywords: HTTP/2; Optimization; Page load time; Performance; Website; HTTP/2; Optimalizace; čas načtení stránky; výkonnost; webová stránka